Time to recurrence and BCLC stage at recurrence as critical variables in guiding treatment decisions for early-recurrent hepatocellular carcinoma after liver resection - Zhang, Jian-Xi; Guo, Luo-Bin; Zeng, Chong-Shi; Huang, Qi-Zhen; Lai, Zi-Sen; Wu, Meng-Meng; Chen, Qing-Jing; Lai, Yong-Ping; Qiu, Xin-Feng; Zhang, Bing; Zhang, Jia-Cheng; Lv, Jia-Hui; et al. (Frontiers in Oncology, 2025)
BackgroundPatients with Barcelona Clinic Liver Cancer (BCLC) stage 0/A hepatocellular carcinoma (HCC) represent the guideline-recommended population for liver resection; however, treatment strategies for early recurrence after resection remain debated. This study aimed to analyze prognostic factors for survival after recurrence (SAR) in patients with early recurrence following R0 resection of BCLC stage 0/A HCC and to develop evidence-based treatment recommendations integrating time to recurrence (TTR) and BCLC stage at recurrence.MethodsWe conducted a retrospective review of 544 patients with early recurrence after R0 resection of BCLC stage 0/A HCC at a tertiary hepatopancreatobiliary academic hospital. Curative treatments included repeat liver resection and ablation, while non-curative treatments comprised transarterial chemoembolization and systemic therapy. Kaplan–Meier methods were applied to estimate SAR, and independent prognostic factors were identified with multivariable Cox regression analysis.ResultsThe median SAR was 39.4 months, with 1-year, 3-year, and 5-year SAR rates of 81.8%, 52.6%, and 39.0%, respectively. Patients receiving curative treatments demonstrated significantly improved SAR compared with those undergoing non-curative therapies (P < 0.001). Multivariable analysis identified TTR, alpha-fetoprotein level, albumin level, BCLC stage at recurrence, treatment modality, and microvascular invasion in initial tumors as independent prognostic factors for SAR. Subgroup analysis showed that integrating TTR and BCLC stage effectively guided treatment allocation: for BCLC stage A or C disease, treatment should follow current BCLC guidelines, whereas for stage B disease, curative therapy conferred survival benefit when TTR was >6 months but offered no benefit when TTR was ≤6 months.ConclusionsCurative treatments remain an effective option for selected patients with early-recurrent HCC. Treatment allocation based on TTR and BCLC stage at recurrence may optimize outcomes for this population.